Distribution trends of European dragonflies under climate change. Issue 6 (12th March 2019) - Termaat, Tim; van Strien, Arco J.; van Grunsven, Roy H. A.; De Knijf, Geert; Bjelke, Ulf; Burbach, Klaus; Conze, Klaus‐Jürgen; Goffart, Philippe; Hepper, David; Kalkman, Vincent J.; Motte, Grégory; Prins, Marijn D.; et al.
Abstract: Aim: Poleward range shifts of species are among the most obvious effects of climate change on biodiversity. As a consequence of these range shifts, species communities are predicted to become increasingly composed of warm‐dwelling species, but this has only been studied for a limited number of taxa, mainly birds, butterflies and plants. As species groups may vary considerably in their adaptation to climate change, it is desirable to expand these studies to other groups, from different ecosystems. Freshwater macroinvertebrates, such as dragonflies (Odonata), have been ranked among the species groups with highest priority. In this paper, we investigate how the occurrence of dragonflies in Europe has changed in recent decades, and if these changes are in parallel with climate change. Location: Europe. Methods: We use data from 10 European geographical regions to calculate occupancy indices and trends for 99 (69%) of the European species. Next, we combine these regional indices to calculate European indices. To determine if changes in regional dragonfly communities in Europe reflect climatic warming, we calculate Species Temperature Indices (STI), Multi‐species Indicators (MSI) and Community Temperature Indices (CTI). Results: 55 of 99 considered species increased in occupancy at European level, 32 species remained stable, and none declined. Trends for 12 species are uncertain. MSI of cold‐dwelling and warm‐dwelling species differ in some of the regions, but increased at a similar rate at European level. CTI increased in all regions, except Cyprus. The European CTI increased slightly. Main conclusions: European dragonflies, in general, have expanded their distribution in response to climate change, even though their CTI lags behind the increase in temperature. Furthermore, dragonflies proved to be a suitable species group for monitoring changes in communities, both at regional and continental level.